Change in disability in patients with multiple sclerosis: a 20-year prospective population-based analysis. Issue 10 (26th February 2008) - Hirst, C; Ingram, G; Swingler, R; Compston, D A S; Pickersgill, T; Robertson, N P
Abstract : Background: In patients with multiple sclerosis (MS), the natural history of the disease is of considerable importance to predict and understand long-term outcome and inform choices made by patients and clinicians. This information should ideally be derived from data that reflects the entire disease course. Methods: In this study, morbidity data from a prevalent cohort established in 1985 have been re-examined after an interval of 20 years to assess factors that may be important in determining outcome. Results: Of 379 patients who fulfilled criteria for definite or probable MS in the original population-based cohort, 221 (58.3%) had died, 149 (39.3%) were alive and 9 (2.4%) were untraceable. Mean Expanded Disability Status Scale (EDSS) score in 1985 was 5.15 (SD 2.7, range 0–9.5) and 8.01 (SD 2.6, range 0–10) in those alive in 2005. Mean worsening of EDSS scores in surviving patients was +3.02 EDSS points, but 14.0% had worsened by <1 EDSS point over 20 years. 61.4% of patients with EDSS 3.5–5.5 and 82.2% of those with an EDSS of ⩽3 in 1985 had an EDSS of ⩾6 after 20 years. Lower baseline EDSS scores (p<0.0001), higher pyramidal functional system score (p = 0.02) and a greater number of functional systems involved (p = 0.001) were significantly more likely to be associated with greater worsening of disability. Of those with benign disease in 1985, only 19% remained benign after 20 years of follow-up; however, 12.6% of patients had minimal disability after at least 20 years after their disease onset and 14% of patients failed to worsen by ⩾1 EDSS point. Conclusions: This study emphasises the importance of long-term epidemiological studies and the development of clinically relevant measures that effectively predict outcome and can guide decisions on therapeutic management.